Hubungan Tingkat Pengetahuan Remaja Tentang Pernikahan dan Berkeluarga dengan Sikap Praktik Pernikahan Dini di SMK Hasyim Asy'ari - Kusumaningsih, Tri Puspa (Lembaga Riset Pengabdian Masyarakat dan Publikasi Ilmiah Institut Teknologi Bhakti Putra Bangsa Indonesia, 2024)
Early marriage according to the World Health Organization (WHO) is a marriage carried out by a couple or one of the partners under the age of 19 years. The results by researchers there was 1 case of early marriage that occurred at SMK Hasyim Asy'ari Purworejo in 2023 because the student was pregnant out of wedlock. This research is an analytical survey research with a cross sectional, the research result data is presented in the form of Kendall Tau-B correlation. The respondents was 30 people with the results of the study of the level of knowledge at SMK Hasyim Asy'ari Purworejo, most of which were 15 (50%) respondents sufficient knowledge, 8 (27%) respondents less knowledge, 7 (23%) respondents good knowledge. The attitude of early marriage practices at SMK Hasyim Asy'ari Purworejo, most of which were 15 (50%) respondents sufficient attitudes, 7 (23%) respondents less attitudes and 2 (7%) respondents good attitudes. The results of bivariate analysis with Kendall Tau-B an alpha value of 0,66 which means the hypothesis is rejected.